Kepastian Hukum Status Terpidana Percobaan dalam Syarat Pencalonan Pilkada Gorontalo Utara 2024 - Sandi Pratama Katili; Erman I. Rahim; Abdul Hamid Tome (Legtimacy: Journal of Law and Islamic Law, 2025)
This study examines the 2024 North Gorontalo regional election dispute regarding the eligibility of probationary convicts. Legislative ambiguity caused conflicting interpretations between the KPU, Bawaslu, and the Constitutional Court. Constitutional Court Decision No. 55/PHPU.BUP-XXIII/2025 adopted a progressive stance, ruling that candidates serving probation are ineligible and must be disqualified, necessitating a revote. While this decision upholds democratic integrity and electoral justice, it reveals inconsistencies when compared to precedents like the Rusli Habibie case. The findings demonstrate that legal certainty concerning candidacy requirements remains suboptimal, specifically regarding the political rights of those under judicial supervision. This research argues that regulatory harmonization and reinforcing the Constitutional Court’s authority are vital to ensuring regional elections are consistent, fair, and responsive. Such legal reforms protect essential constitutional rights of voters within the current local democratic process today in Indonesia to guarantee governmental integrity based upon the highest prevailing laws of the Indonesian legal nation.